Insight into the origin of chikungunya virus in Malaysian non-human primates via sequence analysis - Suhana, O.; Nazni, W.A.; Apandi, Y.; Farah, H.; Lee, H.L.; Sofian-Azirun, Mohd (Elsevier, 2019)
Chikungunya virus (CHIKV) is maintained in the sylvatic cycle in West Africa and is transmitted by Aedes mosquito species to monkeys. In 2006, four verified CHIKV isolates were obtained during a survey of arboviruses in monkeys (Macaca fascicularis) in Pahang state, Peninsular Malaysia. RNA was extracted from the CHIKV isolates and used in reverse transcription polymerase chain reactions (RT-PCR) to amplify PCR fragments for sequencing. Nucleic acid primers were designed to generate overlapping PCR fragments that covered the whole viral sequence. A total of 11,238 base pairs (bp) corresponding to open reading frames (ORFs) from our isolates and 47 other registered isolates in the National Center for Biotechnology Information (NCBI) were used to elucidate sequences, amino acids, and phylogenetic relationships and to estimate divergence times by using MEGA 7.0 and the Bayesian Markov chain Monte Carlo method. Phylogenetic analysis revealed that all CHIKV isolates could be classified into the Asian genotype and clustered with Bagan Panchor clades, which are associated with the chikungunya outbreak reported in 2006, with sequence and amino acid similarities of 99.9% and 99.7%, respectively. Minor amino acid differences were found between human and non-human primate isolates. Amino acid analysis showed a unique amino acid at position 221 in the nsP1region, at which a glycine (G) was found only in monkey isolates, whereas arginine (R) was found at the same position only in human isolates. The time to the most recent common ancestor (MRCA) estimation indicated that CHIKV probably started to diverge from human to non-human primates in approximately 2004 in Malaysia. The results suggested that CHIKV in non-human primates probably resulted from the spillover of the virus from humans. The study will be helpful in understanding the movement and evolution of CHIKV in Malaysia and globally. © 2019 The Author(s)